The messianic commons: images of the messiah after modernity - Blower, David Benjamin (SCM Press, 2024)
Messianic stories run through the Abrahamic faiths and many others besides. Messianism is the religion of the oppressed; the faith of those whose struggle compels them toward alternative futures. Messianism has also become a watchword for visionaries of radical politics, far beyond confessional religious spaces. These sketches explore how we might encounter ourselves differently in the dim light of that illusive figure: how we might reimagine ourselves as ecological creatures, economic agents, and as beings who dance differently with power and life, amidst the many threads of messianic folklore. --